Trainers` understanding of chosing the frequency speed of kick test (FSKT) for taekwondo practitioners - Ferreira da Silva Santos, J.; Franchini, E. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2021)
Aim. The frequency speed of kick test (FSKT) is performed by taekwondo athletes and practitioners in a short version (10s), and an intermittent version (5 sets x 10s effort/10s pause). The purpose of the present study was to determine the views of coaches with different academic backgrounds on the frequency speed of kick test (FSKT). Material, Methods and Results. To start, ten sports scientists with more than 10 years` experience were consulted about the ques-tions. After the final version of the questionnaire was constructed, the experts were asked to answer the questionnaire. 94 subjects participated in the study. They were allocated into one of following three groups: (1) non-graduates (n = 32); (2) graduates (n = 34) and (3) post-graduates (n = 28) in physical education and/or sports sciences. The main results were: a) the subjects consulted considered that the tests were `easy` (48%) or `very easy` (53%) to understand; (b) the application of the tests were considered `practicable` (50%) or `very practicable` (49%); c) most interviewees considered FSKT10s (76%) and FSKTmult (60%) to be predominantly anaerobic. However, for both tests some participants considered them to be predominantly aerobic (FSKT10s = 25%; FSKTmult = 40%). Conclusions. Based on the results of this study, we may conclude that coaches, and strength and conditioning professionals con-sidered that the FSKT is a test that can be applied and understood and mainly assesses anaerobic fitness. However, a different interpretation of the tests` measures is associated with the professional degree of the coach, or strength and conditioning coach.